The role of cultural events in safeguarding the built heritage: comparative study between the events "Constantine, capital of Arab culture" and "Rabat city of lights" - Omeiche, Khoula; Dekoumi, Djamel (Journal of Human Sciences, 2021)
Cultural heritage is an important part of every country; it is in fact a powerful catalyst for economic, cultural and social development; especially for Algeria and Morocco, which are countries rich in built heritage. In this sense, Algeria at its level, did not consider the built heritage as a priority; unlike Morocco, which considered it from the start as a source of wealth (promotion of cultural tourism). The purpose of this article is to analyze and compare two different experiences in the management of built heritage. Through this analysis, we tried to bring out the major differences in management. For Morocco, the mixed project management (public and private) with the diversity of financing is the strong point for this experience, while in Algeria, it should be noted a total absence of private project management and the Algerian state is the exclusive owner of the work through its various local and central organizations.